Az angol nyelvű walesi irodalom fogalmáról és történetéről - Reichmann, Angelika (Studia Litteraria, 2016)
The present article was written as a chapter of a literary historical project which aims to present an overview of English Literature to Hungarian readers. Hence its introductory nature: apart from the works of Dylan Thomas, Welsh writing in English has been hardly translated into Hungarian and is little known. After clarifying the somewhat convoluted term, the article provides a survey of the literary historical periods in Welsh writing in English since its emergence in front of the backdrop of industrialisation and aggressively imperial English language politics at the turn of the 19th and 20th centuries. Then it proceeds to highlight five characteristics of that literature from a postcolonial perspective. Through selective micro-analyses of largely contemporary prose works, the article focuses on such aspects of Welsh writing in English as its concern with language itself (code-switching) and with rewriting Welsh history. In relation to the latter, it discusses the early presence of experimental tendencies and women writers, and the literature’s emphatic and recently “institutionalised” reassessment of the Welsh mythical heritage.